Eplerenone for chronic central serous chorioretinopathy–a randomized controlled prospective study. Issue 7 (27th June 2017) - Schwartz, Roy; Habot‐Wilner, Zohar; Martinez, Michael R.; Nutman, Amir; Goldenberg, Dafna; Cohen, Shai; Shulman, Shiri; Guzner‐Gur, Hanan; Loewenstein, Anat; Goldstein, Michaella
Abstract: Purpose: To evaluate the efficacy and safety of eplerenone for chronic nonresolving central serous chorioretinopathy (CSC). Methods: Prospective, double‐blind, randomized placebo‐controlled study. Nineteen eyes of 17 patients with persistent subretinal fluid (SRF) due to CSC were enrolled and randomized to receive eplerenone 50 mg/day or placebo for 3 months, followed by a 3‐month follow‐up. The main outcome measure was change in SRF from baseline to 3 months of treatment. Secondary outcomes included change in SRF at any time‐point, complete resolution of SRF, improvement in choroidal thickness and change in best‐corrected visual acuity (BCVA). Results: Thirteen eyes were treated with eplerenone and six with placebo. Both groups showed reduction in SRF throughout the treatment period, with a significant reduction at months 1, 3 and 5 only in the treatment group. Twenty‐three per cent in the treatment group and 30.8% per cent in the placebo group experienced complete resolution of SRF. A significant improvement in BCVA was noted in the placebo group at 4 months, as well as a significant difference in BCVA between groups at 3 months in favour of the placebo group (p = 0.005). There was no significant difference in choroidal thickness in either group throughout the study period. No adverse events related to eplerenone were noted in the treatment group. Conclusion: In this study, eplerenone was not found to be superior to placebo in eyes with chronic CSC.